Fatty degeneration and wnt10b expression in the supraspinatus muscle after surgical repair of torn rotator cuff tendon. (5th August 2019) - Kuwahara, Yoshiyuki; Kishimoto, Koshi N; Itoigawa, Yoshiaki; Okuno, Hiroshi; Hatta, Taku; Matsuzawa, Gaku; Itoi, Eiji
Purpose: In the torn rotator cuff muscles, decreased expression of wnt10b prior to elevation of peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer-binding protein α (C/EBPα) has previously been reported. The purpose of this study is to elucidate the expression profiles of these adipogenesis-related genes after rotator cuff detachment and reattachment in a rabbit model. Methods: We investigated gene expression profiles of PPARγ, C/EBPα, and wnt10b in different parts of rabbit supraspinatus (SSP) muscle after tendon detachment ( n = 6 for each time point). In addition, we assessed expression of the same genes after SSP reattachment with different intervals from initial detachment ( n = 6). Fatty degeneration of the SSP muscle was examined by Oil red-O staining. Gene expression profiles were examined by quantitative real-time polymerase chain reaction. Results: After SSP detachment, Oil red-O-positive oil deposits increased after 3 weeks. In the SSP reattachment model, numerous Oil red-O-positive cells were present at 5-week reattachment, following 2- and 3-week detachment. PPARγ and C/EBPα messenger ribonucleic acid expression exhibited a significant increase at 2 and 3 weeks after SSP detachment and remained increased at 5-week reattachment after 2- and 3-week detachment. A decreased expression of wnt10b was observed from 1 week after SSP detachment. Expression of wnt10b was recovered not in the central area of the SSP muscle but in the periphery after reattachment. Adipogenic change was not observed when SSP tendon was reattached after 1-week detachment. Conclusions: These results may suggest that once the adipogenic transcription factors, PPARγ and C/EBPα, were elevated, repair surgery after rotator cuff tear could not prevent the emergence of fat in the SSP muscle.